Data Sources of Child Protection Program Development Planning in The Directorate of Social Rehabilitation for Children, Ministry of Social Republic of Indonesia - Enny Kurniasih; Alfrojems Alfrojems (Asian Social Work Journal, 2021)
Efforts to protect children through social rehabilitation programs are one of the efforts to ensure that children's needs are met in order to realize good quality of the younger generation. Children's social rehabilitation programs have quite specific responsibilities, especially in ensuring that the tools or menus in the program are in accordance with the needs of children's growth and development which are also adapted to current developments, therefore concrete efforts are needed to be able to develop child protection programs in the environment. Directorate of Child Social Rehabilitation, Ministry of Social Affairs of the Republic of Indonesia. To answer these background conditions, the purpose of this study was to determine the source of data for planning the development of child protection programs at the Directorate of Child Social Rehabilitation. This research was conducted with qualitative methods and descriptive types. data collection techniques in the form of study documentation, observation and in-depth interviews. The number of informants in this study amounted to 5 informants with the sampling technique, namely purposive sampling. The results of this study indicate that the source of data for planning the development of child protection programs within the Directorate of Child Social Rehabilitation comes from several activities such as supervision, monitoring, evaluation, reporting, and of course policy reflection.